2008
DOI: 10.1080/01612840802370681
|View full text |Cite
|
Sign up to set email alerts
|

Violent Lives of Women: Critical Points for Intervention/Life Charting

Abstract: Each year, 5.3 million women are abused and several thousand die at the hands of intimate partners. If family violence were better understood, it could be predicted, described by patterns and prevented. Life charting (LC) is a method developed to explicate complex phenomena, such as bipolar disorder. This study tested the feasibility and usefulness of LC in deriving data about critical points in life when interventions could reduce or prevent family violence. Two research questions guided the study: (1) Does L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Structural and symbolic violence is represented through cultural norms and practices that discriminate against girls, such as female genital mutilation, forced marriage, dowry, and honor killing, and pose a violation of human rights in some countries. Structural violence, through the unequal distribution of resources and lack of economic opportunities, is also demonstrated by the forced entry of young children from economically marginalized or disorganized families into sex work, which puts them at risk of sexually transmitted infection and mental health problems [ 51 ]. Homelessness may be another outcome for children and youth from disorganized families [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Structural and symbolic violence is represented through cultural norms and practices that discriminate against girls, such as female genital mutilation, forced marriage, dowry, and honor killing, and pose a violation of human rights in some countries. Structural violence, through the unequal distribution of resources and lack of economic opportunities, is also demonstrated by the forced entry of young children from economically marginalized or disorganized families into sex work, which puts them at risk of sexually transmitted infection and mental health problems [ 51 ]. Homelessness may be another outcome for children and youth from disorganized families [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…We originally obtained institutional review board (IRB) approval to conduct focus groups to explore and describe the experiences of family caregivers of newly injured Latino individuals with SCI within their first 2 years after rehabilitation. We based this approach on the success of focus groups used in previous studies involving sensitive family issues in the Latino population, including SCI, teen sexual behaviors, and intimate partner violence (Brackley & Williams, 2008; Koniak-Griffin & Lesser, 2007; Lesser, Oscós-Sánchez, Tello, Cardenas, 2005; Oscós-Sánchez & Lesser, 2007). After recruitment of study participants began, we realized that family members were reluctant to discuss what was perceived as personal information in a group of people who were unknown to them.…”
Section: Methodsmentioning
confidence: 99%
“…, ). Brackley & Williams () interviewed 21 women who self‐reported experiences of abuse, and they concluded that life charting provides research data that can be used in preventing violence against women. In this study, the life charts are created together with the women using a software program during the interview.…”
Section: Introductionmentioning
confidence: 99%
“…Using the life chart method to visualize a person's life has previously been used within psychiatric care (Chafetz 1996, Ehnvall et al 2003, Livianos-Aldana & Rojo-Moreno 2006, Sunnqvist et al 2007. Brackley & Williams (2008) interviewed 21 women who selfreported experiences of abuse, and they concluded that life charting provides research data that can be used in preventing violence against women. In this study, the life charts are created together with the women using a software program during the interview.…”
Section: Introductionmentioning
confidence: 99%